2020
DOI: 10.1002/ijc.33209
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the journey to breast cancer diagnosis in sub‐Saharan Africa: Findings from the multicountry ABC‐DO cohort study

Abstract: Most breast cancer patients in sub-Saharan Africa are diagnosed at advanced stages after prolonged symptomatic periods. In the multicountry African Breast Cancer-Disparities in Outcomes cohort, we dissected the diagnostic journey to inform downstaging interventions. At hospital presentation for breast cancer, women recalled their diagnostic journey, including dates of first noticing symptoms and healthcare provider (HCP) visits. Negative binomial regression models were used to identify correlates of the length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 39 publications
0
70
0
Order By: Relevance
“…On a positive note, distance to first provider did not contribute to delays or late stage, and many first providers were contacted early in the prediagnostic journey. 22 This first provider thus represents a critical first interaction of the women with the health sys- Nevertheless, in interpreting the results of the present study, potential limitations of the study must be considered. One of the limitations of the study is that the geocodes were based on the names of places that may cover a large area, making the locations less precise.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On a positive note, distance to first provider did not contribute to delays or late stage, and many first providers were contacted early in the prediagnostic journey. 22 This first provider thus represents a critical first interaction of the women with the health sys- Nevertheless, in interpreting the results of the present study, potential limitations of the study must be considered. One of the limitations of the study is that the geocodes were based on the names of places that may cover a large area, making the locations less precise.…”
Section: Discussionmentioning
confidence: 90%
“…These heterogeneities underscore the importance of evaluating the specificities of each population when designing measures for down-staging in SSA.Unlike many of the previous studies of cancer diagnosis in SSAsettings, the present study featured geospatial dimension to prediagnostic journey, which has been underinvestigated in cancer care in SSA. The results of our study, together with the other key determinants of delay in breast cancer diagnosis22 and advanced stage at diagnosis11 (eg, lack of breast cancer awareness), can guide future implementation research and governments and their partners to make informed decisions about the planning and development of strategies to mitigate breast cancer deaths in SSA settings.…”
mentioning
confidence: 90%
“… 49 , 51 , 91 , 92 Individual- and group-level (eg, family or social network) barriers include cancer fear and stigma, poor health literacy, lack of trust in healthcare providers, and low expectations or perceptions regarding healthcare access or quality. 3 , 93 - 98 Such barriers have been associated with demonstrably longer intervals to help-seeking for possible cancer symptoms 99 , 100 and advanced stage at diagnosis among those diagnosed with cancer. 101 , 102 …”
Section: Prompt Help-seeking For Symptomsmentioning
confidence: 99%
“…Postpresentational intervals in LMICs often account for a greater proportion of total time to cancer diagnosis and treatment compared with help-seeking intervals. 98 , 107 Furthermore, focusing on early diagnosis is an important precursor to establishing cancer screening programs by increasing diagnostic capacity for all individuals with positive results. 108 Early diagnosis programs have the potential to contribute to health system development as the diagnosis and treatment of cancer requires a coordinated multidisciplinary approach.…”
Section: Prompt Investigation and Diagnosismentioning
confidence: 99%
“…A long waiting time for test results, more speci cally for the biopsy results, was a factor in uencing the time to treatment in 11 included studies [24,[26][27][28][29][30][32][33][34][35][36]. Seven included studies reported that referral was delayed for women who had visited other health facilities 1 to 4 times or more before visiting the diagnostic centre [23,24,30,[36][37][38][39]. In one of these studies, for instance, more than 80% of 499 patients had at least 3 visits before diagnosis, and repeat visits in the referral system appear to have been caused by misdiagnosis and delays in appointments and test results [24].…”
Section: Health Service Deliverymentioning
confidence: 99%